ANALISA NILAI TAMBAH PENJUALAN JAMUR TIRAM SEGAR DAN KERIPIK JAMUR TIRAM DI DESA BUMIRAHAYU KECAMATAN BUAY MADANG TIMUR KABUPATEN OKU TIMUR - Hariyono (Jurnal Bakti Agribisnis, 2017)
The purpose of this study is to: (1) To know the income of the business of selling fresh oyster mushroom and the manufacture of oyster mushroom chips in Bumirahayu Village, Buay Madang Timur Regency, OKU Timur Regency, (2) To know the value added value of fresh oyster mushroom sales into oyster mushroom chips In Bumirahayu Village, Buay Madang Timur District, East OKU Regency. This research is from January to February 2015 on the cultivation of oyster mushroom and the business of making oyster mushroom chips in Kelompok Wanita Tani (KWT) "Melati" Bumirahayu Village, Buay Madang Timur District OKU Timur Regency with case study method. This study found that the income obtained by oyster mushroom cultivation business is Rp. 10.953.697, - / PP (Rp 2.738.424, - / Month). As for the business of making oyster mushroom kripik is Rp. 988. 437, - / PP (Rp 3.953.748, - / Month). The existence of a considerable income difference causes the business of making oyster mushroom crackers deserve to be developed and added value on the business of making oyster mushroom kripik is Rp. 12.437, - / Kg or Rp. 1.305.937, - / PP (Rp 5,223,748, - / Month) obtained from the final difference with the cost of the raw materials.